Inflammatory bowel diseases : Crohn's disease and ulcerative colitis - Fischer, Sören; Rath, T.; Neurath, Markus (Internist, 2018)
Inflammatory bowel diseases (IBD) are complex diseases. Epidemiological studies suggest rising incidences in industrialized countries. The article is based on a literature search in PubMed and is oriented on the current guidelines published by the European Crohn's and Colitis Organisation. IBD are characterized by chronic diarrhoea, abdominal pain and peranal haemorrhage. Extraintestinal manifestations commonly affect joints, skin, eyes and bile tracts. Early diagnosis and therapeutic intervention determine individual patient outcome. Medical treatment currently includes aminosalicylates, corticosteroids, thiopurines, calcineurin inhibitors and biologicals. IBDs require anti-inflammatory and if necessary immunosuppressive therapy. Due to extraintestinal complications and the possible need for surgical intervention, an interdisciplinary approach is important.
EVALuna2:35158